Genes Encoding the Glycoprotein Hormone GPA2/GPB5 and the Receptor LGR1 in a Female Prawn - Wahl, Melody; Levy, Tom; Manor, Rivka; Aflalo, Eliahu D.; Sagi, Amir; Aizen, Joseph (Frontiers in Endocrinology, 2022)
In vertebrate reproduction, metabolism, growth and development, essential roles are played by glycoprotein hormones, such as follicle-stimulating hormone (FSH), luteinizing hormone (LH) and thyroid-stimulating hormone (TSH), all of which are heterodimers consisting of two subunits, a structurally identical alpha subunit, and a variable beta subunit, which provides specificity. A 'new' glycoprotein hormone heterodimer identified in both vertebrates and invertebrates, including decapod crustaceans, was shown to be composed of the glycoprotein alpha 2 (GPA2) and glycoprotein beta 5 (GPB5) subunits. The putative receptor for GPA2/GPB5 in invertebrates is the leucine-rich repeat-containing G protein-coupled receptor 1 (LGR1). In this study in the giant freshwater prawn, Macrobrachium rosenbergii, we identified and characterized the GPA2 (MrGPA2), GPB5 (MrGPB5) and LGR1 (MrLGR1) encoding genes and revealed their spatial expression patterns in female animals. Loss-of-function RNA interference (RNAi) experiments in M. rosenbergii females demonstrated a negative correlation between MrGPA2/MrGPB5 transcript levels and MrLGR1 silencing and vice versa, suggesting a possible ligand–receptor interaction. The relative transcript levels of M. rosenbergii vitellogenin (MrVg) in the hepatopancreas were significantly reduced following MrGPA2/MrGPB5 knockdown. MrLGR1 loss-of-function induced MrVg receptor (MrVgR) transcript levels in the ovary and resulted in significantly larger oocytes in the silenced group compared to the control group. Our results provide insight into the possible role of GPA2/GPB5-LGR1 in reproduction, as shown by its effect on MrVg and MrVgR expression and on the oocyte development. Here, we suggest that the GPA2/GPB5 heterodimer may act as a gonad inhibiting factor in the eyestalk-hepatopancreas-ovary endocrine axis in M. rosenbergii.